PROTOTIPE ALAT SISTEM SORTIR DIMENSI, BERAT DAN BARCODE KOTA TUJUAN BERBASIS MIKROKONTROLER ARDUINO MEGA 2560 - Edy Supriyadi; Sultan Arfan Dzunnurain; Abdul Multi; Iriandi Ilyas (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT This prototype is a control system for sorting package based on dimensions, weight and the barcode of the destination city of the package. In this prototype, it has Load Cell sensor input as weight input in sorting, Barcode Reader for reading destination city input on the barcode, 2 Hc-Sr04 sensors as item dimension input and infrared sensor as item detection input. As for the output, namely 11 servo motors as actuators, and LCD. This tool works by sorting package into 4 areas of the destination city by reading barcode data for each item and 2 boxes in each area of the destination city, namely motorbike boxes for small items, and car boxes for large items. Package are declared large if the length, width, height, and weight exceed the specified kkm value, which is 10 cm with a tolerance of 1 cm and weight > 100 grams. From the sorting testing process, this tool yielded 93.34% success. Although there are still technical problems with the guider when positioning the goods. Keywords : Sorter, Ultrasonic, Barcode scanner, Load cell, Conveyor, Arduino Mega 2560